2015
DOI: 10.1111/nmo.12540
|View full text |Cite
|
Sign up to set email alerts
|

Vagotomy prevents the effect of probiotics on caspase activity in a model of postmyocardial infarction depression

Abstract: Key Messages• Myocardial infarction induces apoptosis in the amygdala.• Probiotics reverse the increase in caspase activities in the amygdala after MI, and their beneficial outcome is abolished by vagotomy.• This finding underscores vagus nerve involvement in the beneficial effect of probiotics in an animal model of post-MI depression.• Probiotics were administered daily, 14 days before myocardial ischemia and until euthanasia. Vagotomy was induced in designed groups before 40 min of myocardial ischemia. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Some probiotics, such as Bifidobacterium signal to the brain via vagal pathways [64,65]. When the vagal nerve is cut, some probiotics no longer show effects on brain and behaviour [33,66,67].…”
Section: Probiotics Inflammation and The Vagus Nervementioning
confidence: 99%
“…Some probiotics, such as Bifidobacterium signal to the brain via vagal pathways [64,65]. When the vagal nerve is cut, some probiotics no longer show effects on brain and behaviour [33,66,67].…”
Section: Probiotics Inflammation and The Vagus Nervementioning
confidence: 99%
“…These include anxiety and changes in sociability in addition to changes in physiological function, such as neuroinflammation, activation of the stress response, neurotransmission, and neurogenesis (Sherwin et al, 2017 ). Given the importance of the vagus in bacterial signaling from the gut lumen to the CNS (Bercik et al, 2011 ; Bravo et al, 2011 ; Malick et al, 2015 ), this technique together with pharmacological reagents has the potential to help clarify how microbes are communicating with their host, thus revealing mechanisms underlying the beneficial and detrimental effects of colonic microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the positive effects of several probiotics are abolished after vagotomy , it is suggested that the microbiota can interact with vagal afferent nerves, possibly via 5‐hydroxytryptamine signalling . Diminished vagal nerve activity increases inflammation and obesity‐like complications (reviewed by Valentin and Tracey ).…”
Section: Interactions Between Microbiota and The Hypothalamusmentioning
confidence: 99%